Rancang Bangun Sistem Kendali PID Motor DC Berbasis Blynk untuk meningkatkan Efisiensi dan Fleksibilitas - Auditiya Marizka, Dewi; Lastiyan Ashila, Abyan; Agustina Solihah, Aulia; Adi Prasetyo, Haafidh; Riza, Fachri; Wicaksono, Ridho (Jurnal Inovasi Teknologi Terapan, 2025)
Efficiency in setting PID parameters is important in supporting control system performance, especially in automation applications. This research compares two methods of PID settings, namely manually using keypads and LCDs with an online IoT-based way through the Blynk application. The system is designed to control the speed of a 12V DC motor with the response of an FC-51 infrared sensor. Testing is done through an experimental approach by recording the system response to variations in KP, KI, and KD values. The results show that the IoT-based method provides better control efficiency, high flexibility, and ease of data visualization in real time. Blynk also allows storing historical data in graphical form, although it has limitations, such as a maximum limit of sending 30,000 data per month and a limited number of widgets in the free version. Therefore, for future development, it is recommended to use a standalone dashboard or integration with Node-RED to make the system more flexible, secure, and minimal code. Overall, this research shows that the application of IoT to PID control systems can improve the effectiveness of settings and has the potential to be applied more widely in modern automation systems.